Identifying Weakly Correlated Dominating Stocks using Maximum Independent Set - Gimanjar, Yeremia Bertolla; Prastiwi, Diah; Septyanto, Fendy (Persatuan Aktuaris Indonesia, 2025)
In this paper we consider the problem of efficiently finding a (small) set of stocks taken from an index that can replicate the index performance. Furthermore, we add the requirement that the set’s returns have weak correlation with each other. Such a selection of stocks may be useful for investors who want to simplify their analysis of the stock index, trying to capture market movement with reduced risk. To solve this problem, we use maximum independent set, a concept from graph theory. As a case study we consider IDX80 in the year 2024.